Quality of life among general adult people aged 35-75 years living in Baghdad, Iraq - Ali Kareem Durib; Jalil Ibrahim Saleh; Sadoon Ibraheem; Nawar Sahib Khalil; Abdulmajeed Alwan. Hammadi; Irina Stepanenko (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the quality of life among adults in an urban community. Method: The cross-sectional study was conducted from June 2019 to October 2021 in Baghdad, Iraq, after approval from the ethics review committee of the College of Medicine, Al-Iraqia University, Iraq, and comprised adult subjects of either gender. Data was collected by direct interview using the short version of the World Health Organisation quality of life questionnaire after it was modified and translated into the local Arabic language. Data was analysed using SPSS 18. Results: Of the 800 subjects, 496(62%) were males. The overall mean age was 48.7±13 years (range: 35-75 years). There were 439(54.9%) subjects who were married, 602(75.3%) were employed, 516(64.5%) had primary and secondary levels of education, 586(73.3%) had own houses, 717(89.6%) were living in urban areas, and 378(47.3%) had sufficient income. With respect to quality of life, the environmental domain had the highest mean score 64.8±12.3, while the physical domain had the lowest 60.8±13.2. Gender, age, marital status, occupation, educational status, family income and family size were significantly related to general quality of life (p<0.05). Conclusion: Overall quality of life was found to be fair in among the general adult people studied. Keywords: Adult, Quality of life, Satisfaction, Housing, Arabs, Iraq, Marital status, Characteristics, Occupations.